REGENERATION OF Pimpinella pruatjan THROUGH SOMATIC EMBRYOGENESIS - Roostika, I.; Purnamaningsih, R.; Darwati, I.; Mariska, I. (Indonesian Journal of Agricultural Science, 2007)
Pruatjan (Pimpinella pruatjan Molk.) is an Indonesian endangeredplant which has various medicinal properties such asaphrodisiac, diuretic, and tonic. The plant is commonly harvestedfrom its natural habitat, therefore it becomes endangered. Regenerationof pruatjan through organogenesis has been studied,but its shoot multiplication was very low (5 shoots per explant).The study aimed to investigate the best regeneration techniqueof pruatjan through somatic embryogenesis. This research wasconducted at the tissue culture laboratory, Indonesian Centerfor Agricultural Biotechnology and Genetic Resources Researchand Development in 2004-2005. Callus formation of pruatjanwas induced from the petioles and leaves in Driver andKuniyakiâs (DKW) based medium containing 2,4-D combinedwith picloram at the level of 0.5, 1.0, 1.5, and 1.5 ppm. Embryogeniccalli were then transferred into embryo developmentmedium in two ways. First, they were directly transferred intomedia containing IBA/NAA at the level of 0.5, 1.0, and 1.5 ppm.Second, they were indirectly transferred into media containing2.0 ppm 2,4-D and 0.3% casein hydrolysate prior to the IBA/NAA media. Parameters evaluated were fresh weight, dryweight, time initiation of embryogenic callus formation, andtotal number of embryos. The result showed that calli ofpruatjan were successfully induced from the petioles and leaves.The best calli were induced from the leaves in the DKWmedium containing 2.0 ppm 2,4-D and 0.5 ppm picloram.Embryo development of the calli was best if they were firstgrown in the media containing 2.0 ppm 2,4-D and 0.3% caseinhydrolysate then transferred to the IBA/NAA media. The totalnumber of somatic embryos was counted up to 103 on themedium containing 1.5 ppm IBA. This study indicated thatpruatjan somatic embryogenesis regeneration required threedifferent media, i.e. for callus induction, development andmaturation, and for germination.